Analysis of the Relation Between Learning Environment and Economic Condition on Learning Achievement - Imam Hanafi; Donny Dharmawan; Eka Kusumawati; Muhamad Rusadi Letasado; Abdurohim Abdurohim (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze the relationship between learning environment and economic condition on learning achievement. This research uses quantitative methods. Population used in this research are Medan City Private University students. Based on determining the target sample, sample in the research are 50 students from Medan City Private University. Data analysis in this study used a correlation test. The research results show that there is a relationship between learning environment and learning achievement in Medan City Private University students. There is a relationship between economic condition and learning achievement in Medan City Private University students.